2020
DOI: 10.21203/rs.3.rs-17318/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogen Infection Recovery Probability (PIRP) Versus Proinflammatory Anti-Pathogen Species (PIAPS) Levels: Modelling and Therapeutic Strategies

Abstract: Current CoVID-19 pandemic is spreading rapidly worldwide, and it may become one of the largest pandemic events in modern history if out of control. It appears most of the SARS-CoV-2 virus infection resulted deaths are mainly due to dysfunctions or failures of the lung or multiple organs that could be attributed to host's immunodysfunctions particularly hyperinflammatory type disorders. In this brief review and study, a math model is proposed to correlate the Pathogen Infection Recovery Probability (PIRP) versu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…34 A valuable model for correlating the Pathogen Infection Recovery Probability (PIRP) in competition with Pro-inflammatory Anti-Pathogen Species (PIAPS) levels within a host unit was proposed by Shajing Sun. 35 Correspondingly, the mentioned researcher has also reported that the maximum PIRP was exhibited when the PIAPS levels were either equal to or around the PIAPS equilibrium levels at the pathogen elimination or clearance onset. For performing a successful treatment, it is very important to improve the host's PIRP and more important to prevent the cytokine storm.…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…34 A valuable model for correlating the Pathogen Infection Recovery Probability (PIRP) in competition with Pro-inflammatory Anti-Pathogen Species (PIAPS) levels within a host unit was proposed by Shajing Sun. 35 Correspondingly, the mentioned researcher has also reported that the maximum PIRP was exhibited when the PIAPS levels were either equal to or around the PIAPS equilibrium levels at the pathogen elimination or clearance onset. For performing a successful treatment, it is very important to improve the host's PIRP and more important to prevent the cytokine storm.…”
Section: Figurementioning
confidence: 91%
“…Accordingly, their results showed that immune deficiency or imbalance adaptive immune response condition may worsen the COVID-19 patients' condition. [33][34][35] So, efforts to maintain a balanced and optimal immunity focusing on this pathway can help in the prevention, management, and treatment of this disease, as well as providing some important information for the drug development of COVID-19.…”
Section: Figurementioning
confidence: 99%
“…have been identified in shower curtains and showerhead biofilms. Infection shows mild clinical symptoms such as fever, but are also responsible for bacteremia, peritonitis, and pneumonia [27].…”
Section: Bacterial Opportunistic Pathogensmentioning
confidence: 99%